Cultivating resilience in wheat: mitigating arsenic toxicity with seaweed extract and Azospirillum brasilense - Zaheer, Muhammad Saqlain; Aijaz, Nazish; Hameed, Akhtar; Buttar, Noman Ali; Rehman, Shamsur; Riaz, Muhammad Waheed; Ahmad, Ajaz; Manzoor, Muhammad Aamir; Asaduzzaman, Muhammad (Frontiers in Microbiology, 2024)
Arsenic (As) toxicity is a serious hazard to agricultural land due to growing industrialization, which has a negative effect on wheat crop yields. To address this issue, using seaweed extract and Azospirillum brasilense has emerged as an effective strategy for improving yield under stress conditions. However, the combined application of A. brasilense and seaweed extract in wheat crops under As toxicity has not been fully explored. The effectiveness of combining A. brasilense and seaweed extract in reducing As toxicity in wheat production was examined in this study through a 2-year pot experiment with nine treatments. These treatments included a control with no additives and two As concentrations (50 and 70 μM). At 50 and 70 μM, As was tested alone, with seaweed extract, with A. brasilense, and both. Significant results were achieved in reducing As toxicity in wheat crops. Arsenic at 70 μM proved more harmful than at 50 μM. The application of A. brasilense and seaweed extract was more effective in improving crop growth rates, chlorophyll levels, and stomatal conductance. The combined application notably decreased As concentration in wheat plants. It was concluded that applying A. brasilense and seaweed extract not only improves wheat growth but can also improve soil parameters under As toxicity conditions by increasing organic matter contents, boosting nutrient availability, and increasing the production of antioxidant enzymes.